The Essence of Philosophy - Dilthey, Wilhelm (UNC Studies in the Germanic Languages and Literatures, 1954)
Wilhelm Dilthey (1833-1911), the great German humanist, remained a towering figure in Europe long into the twentieth century. Published in 1954, this translation by Stephen A. Emery and William T. Emery was the first English translation of Dilthey's "Das Wesen der Philosophie" (1907) as well as his first work to be translated completely into English, making Dilthey accessible to scholars of the English-speaking world.